THE INFLUENCE OF THE ‘CHINESE FACTOR’ ON THE DEVELOPMENT OF RUSSIAN-CAMBODIAN RELATIONS - Bektimirova, N.N. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
This article considers the specificity of Russian-Cambodian diplomatic relations which cele-brated 60 years in 2016. The author shows that in the 20th century ideological considerations, namely the po-litical rivalry between China and the USSR, largely dominated in bilateral relations. The ‘Chinese factor’ - China being ‘friend number one’ for Cambodia - drastically influenced USSR’s position on most issues relating to this country. The research demonstrates that both Russia and Cambodia are nowadays inclined to implement a purely pragmatic, non-ideological foreign policy, modifying it and their interests depending on the current situation. Thus, the ‘Chinese factor’ - China’s economic domination in Cambodia - can hardly become a major obstacle to the development of Russian-Cambodian relations, at least in the me-dium-term. Russian aspiration to solidify its position as an influential center of an evolving polycentric world demands the building of constructive relations with all ASEAN member states. This approach includes Cambodia - a relatively small country in terms of human, territorial and economic resources. It would also promote a more stable system of international relations in South-East Asia as a whole, while at the same time partially offsetting Chinese political and economic dominance in Cambodia.